Paroxysmal atrial fibrillation and the hazards of under-treatment. (1st January 2016) - Aronis, Konstantinos N.; Thigpen, Jonathan L.; Tripodis, Yorghos; Dillon, Chrisly; Forster, Kristen; Henault, Lori; Quinn, Emily Kate; Berger, Peter B.; Limdi, Nita A.; Hylek, Elaine M.
Abstract: Background and Purpose: Oral anticoagulants are highly efficacious for the prevention of stroke in atrial fibrillation, and are the preferred treatment by current guidelines. The purpose of our study was to assess the utilization of antithrombotic drugs in atrial fibrillation patients at the time of ischemic stroke and the factors associated with their use. Methods: We enrolled 759 consecutive patients admitted with ischemic stroke at Boston Medical Center, Geisinger Health System, and the University of Alabama. To be eligible, patients had to have electrocardiographically-confirmed atrial fibrillation at the time of admission or within 6 months of the index stroke. All stroke events and electrocardiograms were validated by study physicians. Patients with newly diagnosed atrial fibrillation were not eligible. Results: The mean age was 78 years, 43% were male, 19% black, and the mean CHADS2 score is 3.0. Atrial fibrillation was paroxysmal in 31%. At presentation, 181 (24%) patients were taking warfarin only, 96 (13%) both warfarin and aspirin, 294 (39%) aspirin alone, and 189 (25%) no antithrombotic therapy. The mean international normalized ratio was 1.6. Among patients with paroxysmal atrial fibrillation, one in five was taking warfarin. Although increasing stroke risk was associated with a greater likelihood of warfarin use, only 39% of highest risk CHADS2 3–6 were taking warfarin at the time of stroke. Conclusions: Among high-risk individuals with atrial fibrillation, only 37% were taking warfarin at the time of stroke. Paroxysmal atrial fibrillation was associated with the highest risk of not receiving warfarin.